Reading English Islamic Texts: Students' Reading Comprehension, Vocabulary Knowledge, and Religious Literacy - Syamsiah Depalina Siregar; Khairurijal Khairurijal Khairurijal; Ali Jusri Pohan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Reading English texts on Islamic topics has become increasingly important for students at Islamic higher education institutions, as a growing body of academic and religious resources is published in English. However, successful comprehension of these texts requires not only linguistic competence but also sufficient religious literacy to interpret concepts within their appropriate contexts. This study aims to examine undergraduate students' ability to comprehend English Islamic texts by investigating the relationships among reading comprehension, vocabulary knowledge, and religious literacy. Employing a quantitative correlational design, the study involves students from the English Education and Islamic Education departments at an Islamic university. Data are collected through a reading comprehension test based on authentic Islamic English texts, a vocabulary knowledge test, and a religious literacy questionnaire. The findings are expected to reveal the extent to which vocabulary knowledge contributes to reading comprehension and how religious literacy facilitates students' understanding of both the explicit and implicit meanings embedded in Islamic texts written in English. The study argues that reading comprehension in this context extends beyond language proficiency, encompassing students' ability to integrate linguistic knowledge with religious understanding and contextual interpretation. The findings are expected to provide empirical evidence for the development of English for Islamic Studies materials that are linguistically accessible, pedagogically meaningful, and culturally responsive to the needs of students in Islamic higher education.